Nutritional Evaluation and Utilisation of Oil Palm (Elaeis Guineensis) Frond as Feed for Ruminants - Mahmudul Islam, (1999)

(untitled)
Use of plant residues as ruminant livestock feed has been suggested to reduce the feed-cost and recycle the biomass. Physical and chemical characteristics of oil palm (Elaeis guineensis Jacq.) frond (OPF) and utilisation of OPF by ruminant were studied in a series of experiments. The yield of different fractions (leaflets, petiole and midribs) and segments (basal, middle and top) of OPF from different aged palms were measured. Results showed that the yield of OPF from matured (221 years) palm was 13.4 kg, where basal, middle and top segments constituted 53%, 27% and 20%, respectively. The estimated annual yield of petiole, leaflets and midribs were 21.70, 5.51 and 1.59 (OM.t.ha-1) respectively. The whole OPF contained 418.6, 960.8, 65.3, 740.1, 529.5, 210.6, 218.5, 878.8 and 138.8 (g.kg-1) of dry matter (OM), organic matter (OM), crude protein (CP), neutral detergent fibre (NOF), acid detergent fibre (AOF), cellulose (CEL), hemicellulose (HC), total carbohydrates (TC) and non-fibre carbohydrates (NFC), respectively. Calcium (Ca), phosphorus (P), sodium (Na), potassium (K), magnesium (Mg) contents of the OPF were 0.530, 0.108, 0.049, 0.697 and 0.18 g.100g-10M, respectively. Copper (Cu), zinc (Zn), manganese (Mn), iron (Fe) and sulphur (S) contents of the OPF were 2.71, 11.17, 44.66, 106.7 and 0.096 mg.kg-10M, respectively. The in sacco OM degradation value of the OPF at 48h incubation was 37.32g.100g-1. The in vivo digestibility of OM, OM, CP and AOF of OPF were 52%, 56%, 43% and 26%, respectively. Results of the rumen fermentation trials showed that OPF could support an efficient rumen function when used ~50% is included in the diet. Results of effects of different levels of urea and lor molasses on the preservation qualities of OPF and in sacco digestion characteristics showed that mixing molasses reduced the pH of the preserved OPF, while mixing urea increased the pH. The lowest pH (3.98) was observed in molasses (200 g.kg-1DM) mixed OPF and the highest pH (8.65) was in the urea (60 g.kg-1DM) mixed OPF. Mixing of 20, 40 and 60 g.kg-1DM urea with OPF increased the CP level of the preserved OPF by 25%, 38% and 96%, respectively. Mixing molasses and/or urea showed increased digestion characteristics. The pelleting of OPF increased DM, OM, CP, cell content and decreased the cell wall contents of the OPF. Ensiling and pelleting both reduced (P>0.05) slightly the fibrous components (CEl, HC, lignin and silica) of OPF. Moreover, pelleting and ensiling increased (P<0.05) the rapidly disappearing value, extent and rate of digestion of OPF. Determination of digestible nutrient intake of fresh, ensiled and pelleted OPF and its effects on body weight gain of goats were measured. Results indicated that the pelleting of OPF increased the nutrient intake, digestibility, digestible nutrient intake and reduced refusals. The pelleting of OPF mixed with 4% urea, 15% molasses and 2% fish meal increased the digestible DM and OM intake by 80% and 63%, respectively which resulted in an increased body weight gain of the goats. Based on these studies, it can be concluded that OPF is a potential alternative roughage that can be used as a basal ingredient in the diet of ruminants. Fresh, chopped or ensiled OPF can be used up to 50% in the diet and mixing of either urea or molasses can increase the portion of OPF. The results of this study suggest that pelleting is the best way to conserve and handle OPF where almost no refusal can be observed. Moreover, the use of the pellets is convenient and pre-treatments can be easily incorporated during pelleting. Finally, it is suggested that mixed complete pellet can be made by correcting for the nutrients lacking (protein and minerals) in OPF and the use of the mixed pellet would maximise the utilisation of OPF.